CD38 as Immunotherapeutic Target in Light Chain Amyloidosis and Multiple Myeloma—Association With Molecular Entities, Risk, Survival, and Mechanisms of Upfront Resistance - Seckinger, Anja; Hillengass, Jens; Emde, Martina; Beck, Susanne; Kimmich, Christoph; Dittrich, Tobias; Hundemer, Michael; Jauch, Anna; Hegenbart, Ute; Raab, Marc-Steffen; Ho, Anthony D.; Schönland, Stefan; et al. (Frontiers in Immunology, 2018)
Monoclonal anti-CD38-antibodies yield remissions in about one third of relapsed myeloma patients. Depth of response is reported as associated with CD38-expression-height - without a threshold. As basis for clinical trial strategies, we first determined variation of CD38 target-expression including relation to molecular and clinical “high-risk” definitions in AL-amyloidosis, monoclonal gammopathy of unknown significance (MGUS), asymptomatic, symptomatic, and relapsed multiple myeloma. Secondly, we addressed alternative splicing or lack of CD38-expression as potential mechanisms of up-front resistance. We assessed CD138-purified plasma cell samples from 196 AL-amyloidosis, 62 MGUS, 259 asymptomatic, 764 symptomatic, and 90 relapsed myeloma patients, longitudinal pairs of asymptomatic/symptomatic (n = 34) and symptomatic/relapsed myeloma (n = 57) for CD38-expression by gene expression profiling (GEP; n = 1371), RNA-sequencing (n = 593), and flow cytometry (n = 800). CD38-expression was related to chromosomal aberrations, GEP-based assessment of proliferation and risk, and clinical factors. CD38 was expressed in all malignant plasma cell samples at height varying by two orders of magnitude. Expression was significantly lower compared to normal plasma cells with small but significant downregulation in longitudinal sample pairs (GEP, AMM/MM and MM/MMR, respectively). Higher CD38-expression was associated with slower progression to symptomatic and relapsed myeloma and better overall survival in the latter two, but adverse survival in AL-amyloidosis. Molecularly, it was associated with presence of t(4;14) and high-risk according to the UAMS GEP70 risk score. Lower expression was associated with hyperdiploidy but not high-risk aberrations (del17p, gain1q21), GEP-scores or proliferation. Of the two protein coding CD38-transcripts CD38-001 (8-exon, full length) and CD38-005 (truncated), CD38-001 conveyed >97% of reads spanning the respective CD38 splice junction, excluding alternative splicing of receptor binding-sites as mechanism of upfront anti-CD38-treatment resistance. As CD38 was expressed in all plasma cell diseases, upfront resistance against anti-CD38-treatment is thus neither mediated by (complete) absence of CD38-expression nor alternative splicing removing the antibody target sequence, but likely a gradual difference in expression levels.